MENINGKATKAN HASIL BELAJAR MENYIMAK BAHASA INGGRIS SISWA KELAS X.IIS.A SMAN 1 LAWANG KIDUL PADA MATERI TEKS RECOUNT MELALUI PENGGUNAAN MEDIA PODCAST - Bambang Sugiantoro (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
This study aims to improve the learning outcomes of English listening in students of X IIS.A SMA Negeri 1 Lawang Kidul in Even Semester Education Year 2017/2018 on Recount text material through the use of English podcast media. This study is a classroom action research consisting of two cycles. Each cycle consists of planning, implementation, action, observation and reflection. The subjects of this study were students of class X.IIS.A. as many as 28 students consisting of 21 female students and 7 male students. Data collection is done by performing tests and observations. Based on the data analysis of learning outcomes on listening after the action is done on the first cycle, students who complete the study is 60.71%, while in cycle II students who complete learning increased by 85.71%. The results of data analysis concluded that the podcast media can improve the learning result of listening to English text recount in class X.IIS. A. SMAN 1 Lawang Kidul.